2016
DOI: 10.3389/fphar.2016.00290
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Machinery as Relevant Target in Acute Lymphoblastic T Leukemia

Abstract: Various types of non-neuronal cells, including tumors, are able to produce acetylcholine (ACh), which acts as an autocrine/paracrine growth factor. T lymphocytes represent a key component of the non-neuronal cholinergic system. T cells-derived ACh is involved in a stimulation of their activation and proliferation, and acts as a regulator of immune response. The aim of the present work was to summarize the data about components of cholinergic machinery in T lymphocytes, with an emphasis on the comparison of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…A majority of the cells are also capable of producing ACh ( 62 ). ACh has an anti-inflammatory effect, beyond others because ACh decreases TNF production via a posttranscriptional mechanism.…”
Section: Hrv Is More Than the Autonomic Nerve System: Some Physiologimentioning
confidence: 99%
“…A majority of the cells are also capable of producing ACh ( 62 ). ACh has an anti-inflammatory effect, beyond others because ACh decreases TNF production via a posttranscriptional mechanism.…”
Section: Hrv Is More Than the Autonomic Nerve System: Some Physiologimentioning
confidence: 99%
“…The putative involvement of the non-neuronal cholinergic system in the etiology of hematopoietic derived neoplasia is of particular importance in view of various recent reports (16)(17)(18). Several studies have provided evidence demonstrating that blood cells, especially lymphocytes, possess non-neuronal cholinergic components including cholinergic AChRs (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Jurkat, T-cell-derived leukemic cells, increased M3-mAChR expression (26). In addition, it has been proposed that high levels of ACh in T-ALL may act as an autocrine growth factor and play a significant role in leukemia T-cell clonal expansion via shaping of intracellular calcium signaling pathways (18). However, our study showed the lowest expression of both α7-nAChR and M3-mAChR was in T-ALL patients.…”
Section: Relative Expression Levels (% Of Healthy Subjects) ---------mentioning
confidence: 99%
See 1 more Smart Citation
“…The cholinergic machinery is also present in T-ALL blasts, and a more detailed overview of this subject has been reviewed in detail by Dobrovinskaya and colleagues [26]. ACh production by T-ALL cell lines (CEM, HSB-2, Jurkat, MOLT-3, and MOLT-4) is considerably higher when compared to B-ALL cell lines and unstimulated peripheral blood mononuclear leukocytes obtained from healthy donors [23,27].…”
Section: Ach and Cholinergic Receptorsmentioning
confidence: 99%